PENGARUH INTERNET FINANCIAL REPORTING TERHADAP FREKUENSI PERDAGANGAN SAHAM DENGAN TINGKAT PENGUNGKAPAN INFORMASI WEBSITE SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA SELURUH PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2018) - Duka, Dewi Andini Latif; Taslim, Fadli Ali (Jurnal MS, 2020)
Objective: The purpose of this study are: (1) To find out and analyze Internet Financial Reporting (IFR) affect the frequency of stock trading in all companies listed on the Indonesia Stock Exchange; (2) To find out and analyze the role of website information disclosure level in strengthening the relationship between Internet Financial Reporting on the frequency of stock trading in all companies listed on the Indonesia Stock Exchange. Methodology: The number of research samples were 531 companies. The test tool used is a moderated regression analysis (MRA) using statistical package for social scientists (SPSS) as a statistical test tool. Finding: H1 H2, and H3 are accepted at the 5% confidence level. Conclusion: The results showed that: (1) Internet Financial Reporting has a positive and partially significant effect on the frequency of stock trading in all companies listed on the Indonesia Stock Exchange in 2018. The results of this study mean that, companies that apply IFR can increase the frequency of stock trading; (2) The level of website information disclosure as a moderating variable has a positive and significant effect. The results of this study mean that the level of website information disclosure strengthens the relationship between internet financial reporting and the frequency of stock trading. And the more levels of information disclosure can increase the frequency of stock trading.